From Urban Geodiversity to Geoheritage: The Case of Ljubljana (Slovenia) - Tičar, Jure; Komac, Blaž; Zorn, Matija; Ferk, Mateja; Hrvatin, Mauro; Ciglič, Rok (Quaestiones Geographicae, 2017)
The city of Ljubljana lies at the intersection of various geomorphological regions that have strongly influenced its spatial organization. Prehistoric settlements were built on marshland, a Roman town was built on the first river terrace of the Ljubljanica River, and in the Middle Ages a town was built in a strategic position between the Ljubljanica River and Castle Hill. The modern city absorbed all usable space between the nearby hills. This paper reviews some relief features in Ljubljana, their influence on the city’s spatial development, and urban geoheritage. The results indicate new possibilities for urban geoheritage tourism in the Slovenian capital and its surroundings.